Towards an era of official (involuntary) accountability of NGOs in India. Issue 1 (2nd January 2019) - Yesudhas, Ronald
ABSTRACT: In the recent past, governance reforms in India have resulted in the government and corporate sectors making serious efforts to enhance and showcase their accountability to their principals, namely citizens and shareholders. Similarly, NGOs have been pushed to demonstrate their accountability to multiple stakeholders, namely donors, communities and most importantly, the state. This viewpoint highlights this transition and also reflects on the changing contours of NGO accountability debates in India.